MatE transporter affects methane metabolism in Methermicoccus shengliensis and is modulated by methoxylated aromatic compounds - Huan Leng; Dong Wang; Qing Yang; Shuxin Wang; Leizhou Guo; Pengyan Zhao; Yi Chen; Lirong Dai; Guihong Cha; Liping Bai; Frank Delvigne (Communications Biology)
Abstract Methoxylated aromatic compounds, are abundant in subsurface ecosystems. Recently, it was discovered that Methermicoccus shengliensis can convert methoxylated aromatics to methane. Specifically, the MATE family transporters (MatE) and transduction-like protein (Tlp) were hypothesized to play a crucial role in substrate transport. However, their biological function and the transporting model remained unclear. To address this knowledge gap, we employed bacterial two-hybrid and structural model assays to investigate the interaction between Tlp and MatE. Our results revealed that Tlp senses 2-methoxybenzoate and interacts with MatE to facilitate substrate transport. Furthermore, we observed that the matE knock-out mutant significantly impaired the growth and methane production of M. shengliensis when using 2-methoxybenzoate as a substrate, highlighting the essential role of MatE in methoxydotrophic methanogenesis. Overall, our findings suggest that the MatE-Tlp system regulates substrate uptake and methane metabolism in M. shengliensis, providing new avenues for reducing global methane emissions caused by methanogens.